Beamforming network using switch line phase shifter [electronic resource] - 440784 Suhil Sharif M. Ben Omran (2008)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Communication)) - Universiti Teknologi Malaysia, 2008